Authobiography and cultures of childhood - Becchi, Egle (Historia y Memoria de la Educación, 2015)
This paper deals with three topics and four related examples. The first topic is the subjective culture of children and their free discourses about their own feelings and thoughts. The second concerns interpretations of children’s autobiographies and diaries (Misch, Bernfeld, egodocuments, Lejeune). The third refers to parental control of children’s diaries. Four cases exemplify these issues. The first is Freud’s clinical case of little Hans, where a four-year-old child speaks about his fears, thoughts, dreams and desires, asking his father to write what he says. The second is a diary written by a boy living in Holland at the end of the 18th century. His parents suggest that he writes every day about his feelings and about the reason he acts the way he does. The third is the case of a boy living in Berlin during the first half of the 19th century, who writes a diary about his actions, emotions, memories and faults. The boy is reluctant to continue his diary, and after being scolded by his father, stops writing. The last section analyzes some journaux d’enfant of French girls from the 19th century collected by Lejeune, who discusses parental control of girls and models imposed on them. A further analysis of journaux written by French girls at the end of the 20th century highlights the absence of parental control and models. Finally, the author suggests letting children freely express their thoughts and feelings.